TRIBAL FORMULATIONS FOR TREATMENT OF PAIN: A STUDY OF THE BEDE COMMUNITY TRADITIONAL MEDICINAL PRACTITIONERS OF PORABARI VILLAGE IN DHAKA DISTRICT, BANGLADESH - Seraj, Syeda; Jahan, Farhana Israt; Chowdhury, Anita Rani; Monjur-E-Khuda, Mohammad; Khan, Mohammad Shamiul Hasan; Aporna, Sadia Afrin; Jahan, Rownak; Samarrai, Walied; Islam, Farhana; Khatun, Zubaida; Rahmatullah, Mohammed (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
The Bedes form one of the largest tribal or indigenous communities in Bangladesh and are popularly known as the boat people or water gypsies because of their preference for living in boats. They travel almost throughout the whole year by boats on the numerous waterways of Bangladesh and earn their livelihood by selling sundry items, performing jugglery acts, catching snakes, and treating village people by the various riversides with their traditional medicinal formulations. Life is hard for the community, and both men and women toil day long. As a result of their strenuous lifestyle, they suffer from various types of pain, and have developed an assortment of formulations for treatment of pain in different parts of the body. Pain is the most common reason for physician consultation in all parts of the world including Bangladesh. Although a number of drugs are available to treat pain, including non-steroidal, steroidal, and narcotic drugs, such drugs usually have side-effects like causing bleeding in the stomach over prolonged use (as in the case of rheumatic pain), or can be addictive. Moreover, pain arising from causes like rheumatism has no proper treatment in allopathic medicine. It was the objective of the present study to document the formulations used by the Bede traditional practitioners for pain treatment, for they claim to have used these formulations over centuries with success. Surveys were conducted among a large Bede community, who reside in boats on the Bangshi River by Porabari village of Savar area in Dhaka district of Bangladesh. Interviews of 30 traditional practitioners were conducted with the help of a semi-structured questionnaire and the guided field-walk method. It was observed that the Bede practitioners used 53 formulations for treatment of various types of pain, the main ingredient of all formulations being medicinal plants. Out of the 53 formulations, 25 were for treatment of rheumatic pain, either exclusively, or along with other types of body pain. A total of 65 plants belonging to 39 families were used in the formulations. The Fabaceae family provided 7 plants followed by the Solanaceae family with 4 plants. 47 out of the 53 formulations were used topically, 5 formulations were orally administered, and 1 formulation had both topical and oral uses. 8 formulations for treatment of rheumatic pain contained Calotropis gigantea, suggesting that the plant has strong potential for further scientific studies leading to discovery of novel efficacious compounds for rheumatic pain treatment.